2019
DOI: 10.1093/jas/skz085
|View full text |Cite
|
Sign up to set email alerts
|

Palatability in pigs, the pleasure of consumption1

Abstract: Despite the importance of hedonic reactions in pig's intake, feed palatability has been typically inferred from preference or acceptance measures. However, these measures are influenced by factors beyond palatability, such as energy density and hunger. The aim of this study was to evaluate palatability responses in pigs to sweet and umami taste at different inclusions levels. Pigs (24 per experiment) were video recorded while exposed in pairs to different sucrose (Exp. 1) or monosodium glutamate (MSG, Exp. 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…Nowadays, high-potency sweeteners have been widely used in the animal feed for mammals, including pig and ruminants ( Buerge et al., 2011 , Moran et al., 2014 , Ma et al., 2017 ). Owing to the high sweetness and low-calorie, some sweeteners are extensively used to improve the palatability of the feed ( Figueroa et al., 2019 ). Sweet taste is also correlated with feed intake.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, high-potency sweeteners have been widely used in the animal feed for mammals, including pig and ruminants ( Buerge et al., 2011 , Moran et al., 2014 , Ma et al., 2017 ). Owing to the high sweetness and low-calorie, some sweeteners are extensively used to improve the palatability of the feed ( Figueroa et al., 2019 ). Sweet taste is also correlated with feed intake.…”
Section: Introductionmentioning
confidence: 99%
“…Swede have a greater concentration of glucose and fructose as compared to kale [ 11 ]. The sugar content may affect preferences creating a higher hedonic reaction in rats and pigs [ 23 , 28 ]. Swede presented the highest sugar concentration among all brassicas tested in both experiments, however it has been reported that sugar concentration in swede bulbs varies among varieties from 29% to 36% of total DM, as well as glucose and fructose concentrations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption time (time eating at the pan; CT) and approaches (number of times the pan was approached with a consumption result; A) were assessed from the video recordings by focal continuous sampling over the 10 min test period. Palatability was estimated through consumption patterns (CT/A) [ 23 , 28 ]. Diets offered were counterbalanced between pigs and days to avoid possible order bias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to increase palatability is by giving flavor which is useful for flavor enhancement (Figueroa, 2019). In the future, it is necessary to consider the need to add food flavor enhancers to agricultural and food wastes that will be used as feeds.…”
Section: Feed Consumptionmentioning
confidence: 99%